Faktor-Faktor yang Berhubungan dengan Kejadian Diare Pada Balita di Kelurahan Tanjung Pinang Kota Jambi - Astuti, Erwin Hari; Zunidra, Zunidra (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Diarrhea is a condition where a person defecates with a soft or liquid consistency, it can even be just water and the frequency is more frequent (usually three or more times) in one day. The aim of this research is to determine the description and relationship between fly density, maternal education, maternal behavior, maternal knowledge and the incidence of diarrhea. This type of research is descriptive analytic with a cross-sectional design. The test used in this research is the chi-square test. The research results showed that there was a significant relationship between fly density and the incidence of diarrhea (p-Value = 0.000). There is a significant relationship between maternal education and the incidence of diarrhea (p-Value = 0.000). There is a significant relationship between maternal behavior and the incidence of diarrhea (p-Value = 0.005). There is a significant relationship between maternal knowledge and the incidence of diarrhea (p-Value = 0.001). There is a significant relationship between fly density, maternal education, maternal behavior and maternal knowledge with the incidence of diarrhea in Tanjung Pinang Village, East Jambi District, Tanjung Pinang Health Center Working Area, Jambi City.